POPULATION AND MICROHABITAT OF Gonystylus bancanus (Miq.) Kurz IN DANAU PULAU BESAR-DANAU BAWAH WILDLIFE SANCTUARY, SUMATRA - Kusuma, Yayan Wahyu C.; Pribadi, D.O.; Isnaini, Y. (Buletin Kebun Raya, 2013)
Ramin (Gonystylus bancanus) is one of the major timber species that facing high exploitation in Indonesia. This species can only be found on a specific peat swamp habitat, thus it confines its distribution. Information on its current population and microhabitat characteristics is relatively limited. Here, we investigated natural population and microhabitat of ramin in a peat swamp area in Riau Province usingÂ  random transects consist of 46 (100m2) sampling plots. Forty-eight individuals of ramin were found in which 46 of these belonged to G. bancanus, while the other two were different species. The estimated population density of ramin in this area was 7.18Â±2.75 individuals/ha i.e there were approximately seven individuals in each one-ha area of study. The population structure of ramin showed a J-shaped curve bearing many large old trees with few saplings without any seedlings. The microhabitat was investigated using the Discriminant Function Analysis (DFA) and Canonical Analysis, generating two significant variables that discriminated three groups of the population.